2020
DOI: 10.1186/s12871-020-01128-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl starch for perioperative goal-directed fluid therapy in 2020: a narrative review

Abstract: Background: Perioperative fluid managementincluding the type, dose, and timing of administration-directly affects patient outcome after major surgery. The objective of fluid administration is to optimize intravascular fluid status to maintain adequate tissue perfusion. There is continuing controversy around the perioperative use of crystalloid versus colloid fluids. Unfortunately, the importance of fluid volume, which significantly influences the benefit-to-risk ratio of each chosen solution, has often been ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…We observed that the early nonrestricted entry of large amounts of fluid into the bloodstream caused dilution of coagulation factors and reduced platelet function, resulting in further deterioration of coagulation and that the application of LR rehydration fluids during restrictive resuscitation had a lower effect on coagulation than HES. The hydroxyethyl starch could inactivate or degrade the coagulation factor V, factor VIII, and von Willebrand factor through combination [ 17 ]. In addition, hydroxyethyl starch reduces the expression of platelet glycoproteins Ib and IIb/IIIa and inhibits the binding of fibrinogen and activated platelets, thereby inhibiting endogenous coagulation and platelet adhesion and aggregation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the early nonrestricted entry of large amounts of fluid into the bloodstream caused dilution of coagulation factors and reduced platelet function, resulting in further deterioration of coagulation and that the application of LR rehydration fluids during restrictive resuscitation had a lower effect on coagulation than HES. The hydroxyethyl starch could inactivate or degrade the coagulation factor V, factor VIII, and von Willebrand factor through combination [ 17 ]. In addition, hydroxyethyl starch reduces the expression of platelet glycoproteins Ib and IIb/IIIa and inhibits the binding of fibrinogen and activated platelets, thereby inhibiting endogenous coagulation and platelet adhesion and aggregation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyethyl starch could inactivate or degrade the coagulation factor V, factor VIII, and von Willebrand factor through combination [ 17 ]. In addition, hydroxyethyl starch reduces the expression of platelet glycoproteins Ib and IIb/IIIa and inhibits the binding of fibrinogen and activated platelets, thereby inhibiting endogenous coagulation and platelet adhesion and aggregation [ 17 ]. Other studies have demonstrated that hydroxyethyl starch can inhibit platelet function and increase bleeding tendency by blocking ligand binding to surface receptors and nonspecific modification of cell membrane structure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dilutional anemia associated with ANH, however, has been identified as an important risk factor in the development of acute kidney injury (AKI) among patients undergoing cardiopulmonary bypass (1,2). Although albumin can be used for this purpose its scarcity and costs make synthetic colloids such as hydroxyl ethyl starch (HES) and attractive alternative in the perioperative setting (3).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the first generations of high molecular weight HES that were shown to increase bleeding by interference with platelets and coagulation factors (e.g., von Willebrandt factor and fibrinogen), the third generation of HES has a lower-molecular weight (130 kd), a molar substitution ratio of 0.5 and is suspended in a balanced salt solution at a lower concentration (6%) that altogether confer a safer risk profile while keeping the volemic expansion advantage with prolonged IVS persistence and lesser positive fluid balance. [ 51 ]…”
Section: Perioperative Fluid Optimizationmentioning
confidence: 99%